Manual rotations; are they really the safer alternative for rotational vaginal delivery?. (18th April 2012) - Tempest, N; Hart, A; Walkinshaw, S; Hapangama, D
Abstract : Background: Manual rotation (MROT), where the fetal head, is rotated by the operators hand prior to completing the delivery with traction forceps or ventouse, is increasingly being used to correct malposition as an assisted delivery method. The exact details of the procedure of MROT are unclear with no data on its safety; the procedure is mostly mentioned as an aside in the operation note. There are no clear guidelines on the use or documentation of MROT. Aims: To compare the outcomes of MROT deliveries with other methods of rotational delivery in a tertiary hospital. Methods: Retrospective review of all successful MROT deliveries over a 50 month period with reference to successful rotational ventouse (VEN), kielland forceps (KF) and 2 nd stage caesarean sections for malposition (EMCS). Results: 1494 assisted deliveries for malposition (265 successful MROTs) were analysed. Maternal and neonatal outcomes were comparable in all groups. MROT had a higher rate of massive obstetric haemorrhage (2.3% vs VEN (1.2%) vs KF (1.7%) vs EMCS (2.1%)) and admissions to the neonatal unit (12.8% vs VEN (9.6%) vs KF (10.2%) vs EMCS (11%)). Conclusions: The outcome data on successful MROT are not superior to the other methods of rotational deliveries with some areas showing possible worse outcomes. MROT may be more harmful than a traditional rotational delivery performed by a trained obstetrician. If clinicians are to use this method more stringent regulations and training need to be enforced; guidelines produced so that thorough documentation can be used for audit and outcome purposes.